قلق الامتحان وعلاقته بالدعم الأسري لدى طلبة الشهادة الثانوية بمدينة قصر الأخيار: قلق الامتحان وعلاقته بالدعم الأسري لدى طلبة الشهادة الثانوية (Journal of Humanitarian and Applied Sciences, 2026)
This study aimed to examine the relationship between exam anxiety and family support among secondary school students in Qasr Al-Akhyar, Libya, as well as to identify the levels of both variables within the study sample. The study adopted a descriptive-analytical approach. The population consisted of secondary school students in Qasr Al-Akhyar for the academic year 2025–2026, from which a random sample of 150 male and female students was selected.       For data collection, the researcher used a two-dimensional questionnaire covering test anxiety and family support, with 10 items for each dimension measured using a dichotomous scale (Yes/No). Data were analyzed using percentages and Pearson’s correlation coefficient.       The results indicated a moderate level of test anxiety among students, characterized by feelings of tension, fear, and difficulty concentrating. The findings also revealed a strong negative correlation between test anxiety and family support (r = -0.675), indicating that higher levels of family support are associated with lower levels of test anxiety.
Keywords: Exam Anxiety; Family Support; Secondary School Students